PODES: Sebuah Paket Pemograman Potensi Desa di Indonesia - Mubarak, Fadhlul; Nurniswah, Nurniswah; Sundara, Vinny Yuliani; Ulma, Riri Oktari; Prasaja, Ahmad Syukron (Pusat Kajian Demografi, Etnografi dan Transformasi Sosial, 2024)
The study aims to introduce Village Potential Statistics (PODES) in the form of a computer programming package. PODES collects various information about potential (economy, security, health, employment, communication and information, sports, entertainment, development, community empowerment, education, socio-culture, transportation) and challenges (natural disasters, public health, environmental pollution, social problems, and security disturbances) faced by villages in Indonesia, especially Jambi Province.